Body Building in the Hindu Tantric Tradition: The Advantages and Confusions of Scriptural Entextualization in the Worship of the Goddess Kālī". Issue 1 (24th June 2019) - McDermott, Rachel
Abstract : This article investigates what happens when Tantra, a Hindu esoteric system that is based on the interpretation of the human being as a living, ritualized embodiment of scripture, becomes exotericized through a devotional framework. Building upon the work of Gavin Flood, who coins the term "entextualization" to refer to the way a textual tradition is "written upon" or divinizes the human body, we chart the changes in the medieval Sanskrit Tantric tradition of internalizing the Hindu goddess Kālī when it is taken up by eighteenth-century Bengali devotional poets. What is lost when the esoteric comes out into the open?